Late Marriage among the Adults of Bangladesh: Are We Ready for it Right Now? - Manjur, Monia; Sharma, Puneet; Hossain, M d Anwar (South Asian Journal of Social Sciences and Humanities, 2023)
Unlike other cultures around the globe, marriage is considered a social contract and a religious obligation that was performed before having a sexual relationship. Existing literature indicates in Bangladesh despite having so many restrictions late marriage is gaining popularity among the youth and arising as an emerging problem. But what are the reasons for and consequences of such a phenomenon remain unanswered. A sample survey was conducted among the youth. Unmarried students of post-graduate level studying at Jagannath University, Dhaka University, and North South University were selected as samples for the quantitative data. Some case studies were also conducted for qualitative data to supplement survey data. This study found the causes behind late marriage are- respondents were waiting to complete their education, some were not mentally ready to take the responsibility, family did not discuss their marriage as they have elder siblings, did not want to lose their freedom now. A large number of respondents reported that they may have a problem having a baby due to late marriage which is agreed by the result of case studies. A vast majority of the respondents (90%) were found to use masturbation as an alternative way to meet sexual needs which leads to experiencing different psychosocial problems. More than three-fourths (78%) and two-thirds (69%) of respondents blamed late marriage chronologically for depression and loss of focus on work, respectively. This study drew some recommendations to address the reasons for late marriage and overcome its harsh consequences.